The coefficients of each power of x, including the zeroth power which is not explicitly written as part of the numbers not prefixed to any particular power of x, are added separately. In this instance, the result is 15x + 32.
If: 9x+7 = 6x+25 Then: x = 6
6x + 47 = 9x + 11 6x + 36 = 9x 36 = 3x 12 = x
9x + 3 - 6x - 2 = 3x + 1
144
you just add 6x+9x to get 15x then minus 25 from 18 to get -7 thus the answer will be 15x-7
If: 9x+7 = 6x+25 Then: x = 6
6x + 47 = 9x + 11 6x + 36 = 9x 36 = 3x 12 = x
9x + 3 - 6x - 2 = 3x + 1
9x+6 = 6x+15 9x-6x = 15-6 3x = 9 x = 3
no
144
you just add 6x+9x to get 15x then minus 25 from 18 to get -7 thus the answer will be 15x-7
9x-11 = 6x+1 9x-6x = 1+11 3x = 12 x = 4
9x-19=6x+2 so 3x=21 and x=7
3x + 6x +1 = 10 9x = 10 - 1 9x = 9 x = 1
9x + 8 = 6x + 20(- 8 from both sides)9x = 6x + 12(- 6x from both sides)3x = 12(divide both sides by 3)x = 4
In this equation, x=6.